(untitled) (Research, Society and Development, 2022)
Menopause marks a major transition in women’s lives, having mostly symptoms that directly and harshly impact their quality of life. This research aims to determine the prevalence and characterization of the use of herbal medicines in the treatment for menopause in prescriptions in a compounding pharmacy. This is a cross-sectional study of exploratory retrospective nature and quantitative approach. Data were collected in a small, private compounding pharmacy located in Vitória da Conquista, Bahia. The electronic system FórmulaCerta was used for data collection. The results showed the direct relationship of these phytotherapies as non-hormonal therapy in climacteric conditions and the importance of using them as an alternative form of treatment. It was concluded that of the most prescribed herbal medicines were Passiflora, Tribulus Terrestres and Rhodiola Rósea, and the main associations identified were Cimicifuga, Mulberry, Tribulus Terrestres and Isoflavones.